Intellectual Property, Cultural Property and Intangible Cultural Heritage
1 online resource
Keywords: "Intellectual Property, Cultural Property and Intangible Cultural Heritage examines various notions of property, in particular cultural property and intellectual property, and how they are employed in rights discourses by indigenous and local communities around the world. There is a strong historical dimension to the book's exploration of the interconnection between intellectual and cultural property, intangible cultural heritage and indigenous rights discourses. UNESCO conventions, discussions in the World Intellectual Property Organization (WIPO), the Convention on Biological Diversity and the recent emphasis on intangible heritage have provided various discourses and models. The volume explores these developments and conflicts and examines the uses of the notions of cultural heritage and intellectual property in this context. Case studies from Asia and Africa, as well as from Europe, Australia and South America provide a global examination of the key issues surrounding intellectual and cultural property, and intangible heritage making sense of this complex picture."--Provided by publisher.